Properties of Infinite Matrices and Sequence Spaces - Sahani, Suresh Kumar; Tiwari, S.K. (Asian Journal of Science, Technology, Engineering, and Art, 2023)
Some general theorems on the product of matrices and their applications to infinite series have been obtained. All theorems include, as special cases, a set of well-known results. Several specific new results can also be deduced from it.